Pochonia chlamydosporia Advances and Challenges to Improve Its Performance as a Biological Control Agent of Sedentary Endo-parasitic Nematodes - Manzanilla-López, Rosa H (Journal of nematology, 2013)
The nematophagous fungus Pochonia chlamydosporia var. chlamydosporia is one of the most studied biological control agents against plant (semi-) endo-parasitic nematodes of the genera Globodera, Heterodera, Meloidogyne, Nacobbus and, more recently, Rotylenchulus. In this paper we present highlights from more than three decades of worldwide research on this biological control agent. We cover different aspects and key components of the complex plant-fungus-nematode tri-trophic interaction, an interaction that needs to be addressed to ensure the efficient use of P. chlamydosporia as a biopesticide as part of an integrated pest management approach